Population Dynamics of Sylhet City Corporation: A Mathematical Approach - Hasan, Kazi Md. Jahid (International Journal of Scientific Research and Management (IJSRM), 2021)
For the sustainable development of a country or a city, it is important to know the accurate idea of the population of that region. The local authorities can easily implement their various development plans if they know the future scenario of the population. This study aims to forecast the population of Sylhet City Corporation, which was transformed into a city corporation 20 years ago. Three frequently used and popular methods of population forecasting Arithmetic Increase Method, Geometric Increase Method, and Incremental Increment Method are used to forecast the population. Population data from 2001 to 2015 are used to train and data from 2016 to 2021 are used to verify the methods. The average percentage of error of these three methods is about 3%. Among the three methods, the Geometric Increase Method provides the best result with a percentage of error of 0.15655%.